(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In fact, food security is a very broad concept, which, first of all, implies providing the population with consumer goods in accordance with physiological standards. However, it is worrying that recently the growth in food production has lagged behind the growth in population and needs, especially in countries where there are insufficient conditions for the development of agriculture and the processing industry.